1992
DOI: 10.1007/bf00918272
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of salivary immunoglobulin a in relation to age, saliva flow, mood states, secretion of albumin, cortisol, and catecholamines in saliva

Abstract: Salivary immunoglobulin A (IgA) is one characteristic humoral factor of the local immune system in the upper respiratory tract. Epidemiological studies emphasize the importance of secretory IgA in the protection from infections of the upper respiratory tract. However, due to high interindividual variability of secretion of salivary IgA, it remains difficult to define normal ranges. This series of studies focused on identification of factors influencing basal secretion of salivary IgA. The results indicate a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 21 publications
9
61
1
1
Order By: Relevance
“…At least in some situations, it has been demonstrated that when saliva flow rate is artificially stimulated (with, for example, lemon drops), s-IgA concentrations decrease with increased flow, while the s-IgA secretion rate increases with increased flow rate (Brandtzaeg, 1971). Similar findings have been observed when saliva flow was not artificially stimulated (Graham et al, 1988;Kugler et al, 1992;Evans et al, 1993). The relations between saliva flow rate and s-IgA concentration and secretion rate are particularly important, since autonomic arousal associated with stress or negative affect may influence saliva flow rate (Stone et al, 1987b), although the directionality of the effects is uncertain.…”
Section: Introductionsupporting
confidence: 63%
“…At least in some situations, it has been demonstrated that when saliva flow rate is artificially stimulated (with, for example, lemon drops), s-IgA concentrations decrease with increased flow, while the s-IgA secretion rate increases with increased flow rate (Brandtzaeg, 1971). Similar findings have been observed when saliva flow was not artificially stimulated (Graham et al, 1988;Kugler et al, 1992;Evans et al, 1993). The relations between saliva flow rate and s-IgA concentration and secretion rate are particularly important, since autonomic arousal associated with stress or negative affect may influence saliva flow rate (Stone et al, 1987b), although the directionality of the effects is uncertain.…”
Section: Introductionsupporting
confidence: 63%
“…It has been shown that secretion of SIgA is increased by nervous stimulation of the salivary glands, but the exact manner in which the transport is accelerated is not yet understood (35 ). There must be a cutoff limit to the speed of transport, because SIgA concentrations in saliva are known to decrease as saliva flow is stimulated (36 ).…”
Section: Active Transportmentioning
confidence: 99%
“…6 Salivary IgA is undetectable at birth but then consistently increases with age. 7 The levels of sIgA reach their approximate peak by seven years of age and remain consistently high during mid-life and then decline during old age. 7 Gender differences in sIgA levels have been reported in healthy young men and women.…”
Section: Immune Biomarker: Salivary Immunoglobulin-amentioning
confidence: 99%
“…7 The levels of sIgA reach their approximate peak by seven years of age and remain consistently high during mid-life and then decline during old age. 7 Gender differences in sIgA levels have been reported in healthy young men and women. 8 Serum levels of IgA have not been shown to have direct relationship with those found in saliva.…”
Section: Immune Biomarker: Salivary Immunoglobulin-amentioning
confidence: 99%
See 1 more Smart Citation